Neptune frost [videorecording (DVD)] - Williams, Saul; Williams, Saul; Isheja, Cheryl; Ngabo, Elvis; Free, Kaya; Umuhire, Eliane; Rugamba, Dorcy Ingeli; Muyco, Rebecca; Onekey, Eric; Niyongabo, Trésor; Muziramakenga, Natacha; Kayirebwa, Cécile, 1946- (Kino Lorber, 2022)
Multidisciplinary artists Saul Williams and Anisia Uzeyman bring their unique dynamism to this Afrofuturist vision. It is a sci-fi-punk-musical that's a visually wondrous amalgamation of themes, ideas, and songs that they have been exploring in their work, including on Williams' 2016 album MartyrLoserKing. It takes place in the hilltops of Burundi, where a group of escaped coltan miners form an anti-colonialist computer hacker collective. From their camp in an otherworldly e-waste dump, they attempt a takeover of the authoritarian regime exploiting the region's natural resources, and its people. When an intersex runaway and an escaped miner find each other through cosmic forces, their connection sparks glitches within the greater divine circuitry.